Office interior: the influence of office environmental factors towards task performance - Awang, Arita Hanim; Denan, Zuraini; Abdul Majid, Noor Hanita (Science Publishing Corporation Inc, 2018)
Office environment has become crucial in providing comfort for the workers and in maintaining the sustainability of an office. Office environmental comfort is significant to office workers life as the office has become their second home. Almost half of the five working days were spend in the office. Air conditioning and lighting are among the most significant contributors to high energy consumption in office building in Malaysia. In promoting an energy efficient building, consumption of electrical lighting and air condition in office from morning till evening requires an investigation. The aim of the research is to explore the environmental condition of office which occupied by design related field employees. The environmental air condition and lighting preference are among the significant variables tested. A controlled experiment of a mock-up office with combination of those variables was conducted. The findings indicate that the office workers can still perform their task in extreme conditions which are low level of lighting below 200 lux with highest or lowest temperature between 16 to 32 Degree Celsius, however, the percentage of completion (POC) of the AutoCAD drafting task relatively decreasing. This scenarios show that the designers’ office environmental conditions have significant impact towards task performance. The optimum office environmental setting is needed in order to increase employee’s task performance.